Circular Packaging Innovation Using Pineapple Leaf Fiber (PALF) for Sustainable FMCG Systems (Journal of Advanced and Applied Science and Technology, 2025)
The increasing dependence of the Fast Moving Consumer Goods (FMCG) industry on fossil-based plastic packaging presents significant environmental and regulatory challenges, particularly in countries with high consumption volumes and limited waste management capacity. Indonesia, as an agrarian nation, generates abundant agricultural residues that remain underutilized, including pineapple leaf waste. Pineapple Leaf Fiber (PALF) offers favorable mechanical properties and biodegradability, making it a promising alternative material for sustainable packaging applications. This study adopts a design-oriented applied engineering methodology to develop PALF-based smart composite packaging aligned with biological circular system principles. Pineapple leaf fibers were processed through mechanical decortication, surface treatment, and controlled drying, then incorporated into bio-based polymer matrices at 40–50% fiber content. Composite packaging structures were fabricated using compression molding or lamination techniques adaptable to existing FMCG production lines. Performance evaluation was conducted at laboratory and pilot scales (TRL 5–6), focusing on mechanical durability, moisture resistance, and manufacturability, alongside feasibility and techno-economic assessments. The findings indicate that PALF-based composites provide adequate mechanical strength and flexibility for both flexible packaging and protective layers, while bio-based barrier coatings effectively address moisture sensitivity without compromising biodegradability. Although initial production costs exceed conventional plastic packaging, long-term stability is supported by local raw material availability and reduced exposure to fossil-based price volatility. The study demonstrates that PALF smart composite packaging represents a viable pathway toward sustainable FMCG packaging, integrating material performance, circular resource utilization, and shared economic and environmental value creation.